National Trends and Hospitalizations Related to Pancreatic Cancer in Acute Pancreatitis Patients: A Nationwide Inpatient Sample Study - Gayam, Vijay (Cureus, 2019)
Background Pancreatic cancer (PC) is one of the common cancers in the United States (U.S.) and is associated with high mortality and morbidity. In spite of the modest improvement in survival, cancer care costs including PC continue to rise and inpatient costs contribute a significant chunk to cancer care, which is often ignored. Acute pancreatitis (AP) is a rare manifestation of PC. This study aims to determine the national trends and associated health care utilization of PC patients hospitalized with AP in the U.S. Methods We used National Inpatient Sample (NIS) to extract data for patients hospitalized with a primary diagnosis of PC in AP in 2016 using International Classification of Diseases, 10th revision, and Clinical Modification (ICD-10-CM) codes. The analysis included disease etiologies, age, race, sex, hospital region, hospital size, institution type, mortality, length of hospital stay (LOS), and commonly associated comorbidities were correlated. Results There were 250 patients with a discharge diagnosis of PC in patients admitted with AP. Most of the patients were whites (76.6%) with the mean age of 39.42 ± 2.51 years, had Medicare (63.26%) as primary insurance, were from Southern region (46%) and had higher Charlson comorbidity index (CCI) (76.00% with CCI > = 3). The mean hospital charges were $48,462.13, and mean LOS was 5.24 days. The LOS was significantly impacted by race, hospital region, endoscopic retrograde cholangiopancreatography (ERCP), and comorbidities such as dementia, smoking, and seizure. Out of the 250 patients admitted with PC, 245 patients (98%) were discharged alive. Conclusions Our study shows a downward trend in LOS, hospital charges, and in-hospital mortality as compared to other studies despite PC and AP presenting together versus PC with or without other etiologies.